Gabon : Staff Report for the 2003 Article IV Consultation and Staff-Monitored Program-Staff Report. (IMF Staff Country Reports; Country Report ;, 2004)
The continued decline in oil production and the absence of sustained adjustment policies have contributed to Gabon's uneven economic performance over the past three years. To strengthen further the track record before discussing a possible IMF-supported program, a staff-monitored program has been established for the period September-December 2003. The authorities emphasized their determination to confront the challenges facing the country by pursuing policies aimed at diversifying the economy, sustaining growth, and reducing poverty while containing financial imbalances.